Study Analysis of Three Phase Induction Motor Starting Using ETAP at PLN ULPL Indralaya, South Sumatera - Thriskadewi Umi Rasyda; Letifa Shintawaty (Universitas Panca Marga, 2025)
Steam Generator of Electricity Power Plant at PT. PLN (Persero) UPDK Keramasan of ULPL Indralaya, South Sumatra Area. This power plant has 3-phase induction motors, which are the most commonly used motors because of their reliability. The 3-phase motor is directly connected to the supply at a high starting current of around 5 to 7 times the motor rating current (nominal current). This large starting current can cause a considerable voltage drop on the supply line, thus affecting other loads connected to the supply line. Because the large current flows for a long time, it causes the motor to heat up, which will damage the insulation. Therefore, when starting the motor, the motor bus voltage must be kept at around 80% of the voltage rating. This study investigates whether the motor could start successfully under the operating conditions. We used ETAP software to simulate motor starting and also analyze these motors is to obtain the values of starting current, starting torque, and voltage drop from the results of using VFD (variable frequency drive) on two motor units in LV Switchgear SUS-1 whose previous existing conditions were using DOL (direct on line). A result of our studies, we found that the system can still maintain a bus voltage of 99.94%, a small starting current when starting the motor of 0% FLA (1 second), and reaches 99% FLA (4 seconds) with a starting torque of 54% & 57% of the load torque.